A relativização da coisa julgada nas ações de investigação de paternidade junto ao STJ : uma análise histórica, de casos e o conflito "segurança x justiça" - Gonçalves, Romero Vieira (2011)
This study seeks to discuss the relativization of res judicata in actions of investigation of paternity. It deals with the exceptional hypothesis in which the objective the deconstitution of a sentence wich become already finished, with a deadline for bringing the rescission has passed, due to the advent of a new evidence, the DNA exame, which can demonstrate that the sentence undercover the mantle of res judicata may be flawed. The lawyers, facing this situation, often joining with an autonomous action aimed at reform of the decision, because there is no other remedy applicable, for the duration of action for rescission have been exhausted. In these legal actions often requires the examination of DNA, now joins the other application the report of the examination, because it has already been done (and demonstrates that the sentence, covered up the mantle of res judicata, is wrong) .Given this situation, extraordinary and unusual, there was a great concern in doctrine, but also in the courts, because what is the best solution: to relativize the res judicata or keep it? In answering this question the lawyers always end up saying the conflict between security and justice. The relativistic point that justice must prevail, since the non-relativistic point that should place the principle of legal certainty. The study includes some innovative features, such as the detailed study of all cases decided by the Superior Court of Justice (STJ), which is made a detailed percentage of cases that were for and against the theory of relaxation of res judicata, which enables understanding of how they developed the theory of relativity of res judicata before the Supreme Court. Another innovation is the attempt to show the conflict between security and justice on another aspect, something already done by other scholars, in works on other subjects (such as the legal philosophy), but not done yet in the case of relativization of res judicata in actions of paternity